Precipitation amounts triggering landslide processes in the western part of the Nałęczów Plateau (Lublin Upland, Poland) - Demczuk, Piotr; Zydroń, Tymoteusz; Szafran, Tomasz (Quaestiones Geographicae, 2022)
This study covers the western part of Poland’s loess Nałęczów Plateau (Kazimierz Dolny, Zbędowice). Mass movements in the Lublin Upland occur during periods of increased precipitation or after a snowy and cold winter. To date, there are no comprehensive studies on active (precipitation, hydrology, vegetation, land use, anthropogenic factors) or passive factors (lithology, slope angle) causing such geohazards in this region. This area’s formations are characterised by high sensitivity to even small changes in moisture content; thus, their geotechnical parameters deteriorate as a result of precipitation or rising groundwater levels. The calculations in this study were chosen to determine the time necessary for ground response to external factors, in addition to determining the impact of these factors on decreases in the factor of safety (FS). Based on calculations in GeoStudio software, the impacts of rainfall totals and duration on slope failure, interpreted as an event where the FS falls below 1.0, were analysed. Accordingly, the threshold rainfall value was determined as the total rainfall at the time of slope failure. The study’s results indicate that loess covers are characterised by average water permeability, relatively high internal friction angles and low cohesion, which, combined with high slope inclination, favour landslide formation even when the slope is only partially saturated. The most unfavourable stability conditions occur at the beginning of spring, indicating that loess stability is significantly affected by snowmelt and precipitation at the beginning of the vegetation season, as well as the occurrence of episodic intense precipitation during the summer.